Colorants and Antioxidants Deriving from Methylglyoxal and Heterocyclic Maillard Reaction Intermediates - Leon Valentin Bork; Maximilian Baumann; Tobias Stobernack; Sascha Rohn; Clemens Kanzler (Antioxidants, 2023)
The Maillard reaction is well known for producing antioxidant compounds alongside colored substances. Low-molecular-weight antioxidant intermediates such as maltol (MAL) or norfuraneol (NF) are well described, but it is still unclear which of these Maillard intermediates are the precursors of antioxidant and colored melanoidins—the so-called late stage Maillard reaction products. This study aimed to provide novel insights into the correlation between browning potential and antioxidant properties of reaction products formed during the heat treatment of prominent Maillard reaction intermediates. It was achieved by the incubation of binary reaction systems composed of methylglyoxal (MGO) or NF in combination with furfural (FF), MAL, and pyrrole-2-carbaldehyde (PA) at pH 5 and 130 °C for up to 120 min. Overall, it could be shown that the formation of colored products in the binary NF reaction systems was more efficient compared to those of MGO. This was reflected in an increased browning intensity of up to 400% and a lower conversion rate of NF compared to MGO. The colorants formed by NF and FF or PA (~0.34 kDa and 10–100 kDa) were also found to exhibit higher molecular weights compared to the analogue products formed in the MGO incubations (<0.34 kDa and 10–100 kDa). The incorporation of NF into these heterogenous products with FF and PA resulted in the preservation of the initial antioxidant properties of NF (p < 0.05), whereas no antioxidant products were formed after the incubation of MGO.